HUBUNGAN PERAN ORANGTUA DENGAN TINGKAT KECEMASAN ANAK USIA PRASEKOLAH YANG MENGALAMI HOSPITALISASI DI RS BHAYANGKARA MANADO - Lonto, Chindy (Journal Of Community & Emergency, 2024)
Hospitalization of preschool age children causes anxiety, the role of good parents can minimize children's anxiety. The purpose of the study was to determine the relationship between the role of parents and the level of anxiety of pre-school aged children who were hospitalized at Bhayangkara Hospital Manado. This research is descriptive analytic with cross sectional approach using Chi-square test data analysis. The population is all pre-school-aged pediatric patients who are hospitalized and their parents who are treated in the children's room at Bhayangkara Hospital Manado as many as 58 patients. The results of the research on the role of parents in the less category are 17 respondents (29.3%), the good category is 41 respondents (70.7%) and the child's anxiety level is in the severe category 17 respondents (29.3%), the medium category is 19 respondents (32.8 %), and light category 22 respondents (37.9%). The conclusion is that the result (p_value = 0.000) means that there is a relationship between the role of parents and the level of anxiety of pre-school age children who are hospitalized at Bhayangkara Hospital Manado. Suggestions that this research can be useful for research sites, educational institutions, and further research.